Tinjauan Hukum Islam Terhadap Jasa Titip pada Praktik Jual Beli Tiket Konser di Platform Twitter - Tri, Meliyana Eka Putri; Nurhayati, Agustina; Nur Kholidah, Susi (Jurnal Iqtisad, 2025)
The transformation of information technology in the digital era has revolutionized trade, with buying and selling now shifting to online platforms such as Twitter. One innovation that has emerged is the "jasa titip" (Entrusted Service), where individuals purchase goods or services at the request of others and receive a fee in return. The entrusted service for concert tickets has become increasingly popular among young people, providing fans with ease in obtaining tickets for international artists' concerts. The aims of this research are to examine the practice of buying and selling concert tickets through entrusted service on the Twitter platform and to review the Islamic legal perspective on entrusted service in the context of concert ticket sales on Twitter. This study employs a qualitative descriptive research approach based on fieldwork. The primary data sources consist of interviews with service providers of concert ticket sales on Twitter, while secondary data is obtained from mass media, books, journals, and other references. The methods for data collection in this research include observation, interviews, and documentation. The findings indicate that this practice meets the requirements of a clear contract, utilizing the wakalah (agency) contract, where service providers act as representatives for customers. The clarity of information regarding prices and ticket availability reduces gharar (uncertainty). Service providers also implement security measures to protect customer data and are committed to addressing complaints fairly. This research demonstrates that the market potential for jasa titip concert tickets on Twitter remains promising, despite facing challenges. Transformasi teknologi informasi di era digital telah merevolusi cara perdagangan, dengan jual beli kini beralih ke platform daring seperti Twitter. Salah satu inovasi yang muncul adalah jasa titip (jastip), di mana individu membeli barang atau jasa atas permintaan orang lain dan menerima imbalan biaya. Jasa titip tiket konser semakin populer di kalangan anak muda, memberikan kemudahan bagi penggemar untuk memperoleh tiket konser artis internasional. Jenis penelitian yang dilakukan adalah penelitian deskriptif kualitatif yang bersifat lapangan. Sumber data utama berasal dari wawancara dengan penyedia layanan titip jual beli tiket konser di platform Twitter, sementara sumber data sekunder diperoleh dari media massa, buku, jurnal, dan referensi lain. Metode untuk mengumpulkan data dalam penelitian ini meliputi observasi, wawancara, dan pengumpulan dokumentasi. Temuan penelitian menunjukkan bahwa praktik ini memenuhi syarat adanya akad yang tegas, dengan menggunakan akad wakalah, di mana penyedia layanan bertindak sebagai perwakilan untuk pelanggan. Kejelasan informasi tentang harga dan ketersediaan tiket mengurangi gharar. Penyedia jasa juga menerapkan langkah-langkah keamanan untuk melindungi data pelanggan dan berkomitmen menyelesaikan keluhan secara adil. Penelitian ini menunjukkan bahwa potensi pasar jasa titip tiket konser di Twitter tetap menjanjikan meskipun menghadapi tantangan.